Spray-dried Probiotic adjunct with in vitro acid and bile salt tolerance - Ameeta Salaria; Arora, Shalini; DK Thompkinson; Latha Sabikhi (Indian Journal of Dairy Science, 2023)
Probiotic Lactobacillus acidophilus LA1 was encapsulated using spray drying of concentrated skim milk with total solids (17%) and maltodextrin (25%), and gum acacia (15%) as carriers. The encapsulated probiotic was assessed for viability following drying at an inlet temperature 170°C ± 3°C and an outlet temperature of 80 ± 3°C. The viable count enumerated after drying was 108 log cfu/ml. The prepared probiotic adjunct was further accessed for viability through in vitro acid and bile salt exposure assay. The results indicated that the cell count decreased at lower pH (1, 2) and high incubation periods 1hr and 2hr. A similar trend was observed with bile. However, they showed better survivability for different incubation periods at low pH as well as in high bile salt concentrations. The spray-dried probiotic adjunct was kept for storage at three different temperatures for 8 weeks and assessed weekly for cell viability. An inverse relationship was found during storage in relation to temperature.